Efisiensi Kinerja BAZNAS Bogor Dan Sukabumi: Pendekatan Data Envelopment Analysis - Siti Nurhasanah; Deni Lubis (Jurnal Akuntansi dan Keuangan Islam, 2017)
This study aims to know how performance efficiency BAZNAS in Bogor city, Bogor district, and Sukabumi district, and recommends things need BAZNAS have not been efficient can reach 100 percent efficiency level. This research using Data Envelopment Analysis (DEA) method, with intermediation approach and production approach. The input and output intermediation approach are collected funds, operational costs, and channeled funds. The input and output of production approach are operational costs, socialization costs, collected funds, and channeled funds. The result of this study show that with intermediate approach BAZNAS has descresed efficiency. Calculation of production approach indicates that BAZNAS has increased efficiency value. Badan Amil Zakat Nasional Sukabumi district has obtained efficiency 100 percent in the both approaches. Badan Amil Zakat Nasional have not been efficient can diminished operational cost and socialization cost, then increased collected funds and channeled funds.